Enhanced electrochemical performance of Li-S battery via structural transformation of N, O dual-doped carbon host material. (10th October 2021) - Liu, Jianchao; Chen, Tianrui; Li, Ruhong; Sun, Shuting; Liu, Chen; Mu, Deying; Wan, Weihua; Wang, Zhen; Wei, Junhua; Tian, Shuang; Dai, Changsong
Abstract: Poor electronic conductivity and "shuttle effect" as well as large volume change during cycling hinder the further practical applications of lithium-sulfur batteries (LSBs). Here, N, O dual-doped carbons were developed as sulfur host with adjustable porosity, graphited degree and surficial chemistry by simply changing molten inorganic salts (none, NaCl, NaCl/FeCl3 ) during sintering with aniline-pyrrole copolymer. NaCl promotes the graphitization and porosity with multi-scaled porous carbon host (CH2). NaCl/FeCl3 boosts doping content and facilitates transformation of both chemical state of doping elements and morphology to micro-meso pores dominated nanosheet (CH3) from little porous bulk (CH1). The flexible CH3 nanosheet with micro-mesopores could physically block dissolved Li2 Sn (4 ≤ n ≤ 8) and provide large interfacial area to guarantee good electronic conductivity and ionic transport of the sulfur cathode for improving the electrochemical reactions kinetics. Furthermore, the high content doped pyrrolic N and epoxidized O in CH3 enhance chemical adsorption of soluble Li2 Sn and accelerate the conversion process between Li2 Sn and Li2 S2 /Li2 S. Hence, CH3/S system exhibits ∼30% and ∼167% higher capacity than CH2/S and CH1/S after 200 cycles at 0.2 C. Our results clarify the working mechanism of carbon morphology and nitrogen, oxygen co-doping state tuning and promote the development of high-electrochemical performance LSBs. Graphical abstract: Image, graphical abstract